Dependence of adsorption/diffusion processes in porous media on bulk and surface permeabilities - Albers, B. (Archives of Mechanics, 2001)
The paper contains a macroscopic continuum model for adsorption in porous materials (B. Albers [1, 2]) which is an extension of the model for porous bodies by K. Wilmański [7] on mass exchange processes. We consider the flow of a fluid/adsorbate mixture through channels of a solid component. The fluid serves as carrier for an adsorbate whose mass balance equation contains a source term. Due to low adsorbate concentration we deal with a physical adsorption process which means that particles of the adsorbate stick to the skeleton due to weak van der Waals forces. The model contains two different permeability parameters whose nature is completely different: The first one, the usual bulk permeability coefficient, describes the resistance of the skeleton to the flow of the fluid/adsorbate mixture. The second one describes the surface resistance to the outflow of the mixture from the solid. This work shows within a simple example the range of these parameters and the dependence of adsorption/diffusion on them.